Overview And Evaluation Of The Family Caregivers Of Oncology Project: Improving Quality Of Life And Quality Of Care (Journal of Namibian Studies : History Politics Culture, 2023)
First, I introduce the Family Caregivers of Oncology Project (FCOP). After player's health benefits and a business case for investment in extra care network syndication is made, the continuing publication then evaluates FCOP.